The Educational Advising in Brazil and the municipal education network context of Santa Maria, RS (Research, Society and Development, 2019)
This article is a cross-section of the first author's Master's Thesis in Humanities and Languages Teaching at Franciscana University/RS. The goal is to present the historical context of the Educational Advising in Brazil evidencing the reality of the municipal of Santa Maria, RS, throughout this process. The methodology adopted consists of a qualitative research of the bibliographical and documentary type. Thus, from the historical moments both national and local, it can be observed that the Educational Advising had a diversity of functions that throughout the history has led in disrepute and disagreements about the role of this professional in the management team of schools. It is concluded that highlighting the historical context of Educational Guidance is of fundamental importance so that the role of this professional is valued, enabling the contribution to the challenges of school management, acting as part of a management team